[Kościół św. Bartłomieja w Gdańsku] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia kościół św. Bartłomieja, od zach. widoczny fragment ul. Gnilnej (Faulgraben), ok. 1900 r.